2010
DOI: 10.1038/ijo.2010.206
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactivity at rest and during exercise in middle-aged obese men: effects of short-term, low-intensity, exercise training

Abstract: Objective: Although increased blood flow (BF) in exercising muscles is thought to be impaired in obese subjects and may contribute to physical inactivity, data are scarce in this regard and the involvement of endothelium dysfunction remains partly hypothetical. Methods: A total of 16 middle-aged obese men (body mass index, BMIX30 kg m À2 ) and 16 normal-weight men (BMIo25 kg m À2 ), matched for age, were recruited. We used ultrasonography to compare intima-media thickness (IMT) and distensibility of the caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
5
31
0
1
Order By: Relevance
“…In the present study, the obese patients exhibited a higher intima-media thickness and a lower flow-mediated vasodilation than the healthy controls (see Table 1). Furthermore, both Vinet et al 22) and the present study demonstrated that the HOMA-IR is a predictor of vascular impairment.…”
Section: Carotid Artery Ultrasoundsupporting
confidence: 72%
See 1 more Smart Citation
“…In the present study, the obese patients exhibited a higher intima-media thickness and a lower flow-mediated vasodilation than the healthy controls (see Table 1). Furthermore, both Vinet et al 22) and the present study demonstrated that the HOMA-IR is a predictor of vascular impairment.…”
Section: Carotid Artery Ultrasoundsupporting
confidence: 72%
“…Other previous reports comparing obese subjects and normal weight controls have shown that increased body fat, with a parallel increase in BMI, is linked to vascular damage [20][21][22] . In the present study, the obese patients exhibited a higher intima-media thickness and a lower flow-mediated vasodilation than the healthy controls (see Table 1).…”
Section: Carotid Artery Ultrasoundmentioning
confidence: 99%
“…The CIMT is a direct measure of atherogenesis [35], whereas the Framingham score is a probability of a cardiovascular event established from a cluster of indexes: age, smoking status, type 2 diabetes, blood pressure, LDL and HDL-cholesterol [15]. Despite observed improvements in the Framingham score and carotid-intima-media-thickness, values failed to reach the control group, but remained better than baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired endothelial function, which appears long before symptoms [10], has been consistently demonstrated in the macro-and microcirculation of individuals with type 2 diabetes (Table 1) in association with hypercholesterolaemia, hyperglycaemia, low-grade systemic inflammation and oxidative stress [11]. However, whether VSM function, usually preserved in obese individuals [12], is also impaired in those with type 2 diabetes has been debated in the last two decades, because of discrepant results in both the macro-and microcirculation (Table 1).…”
Section: Introductionmentioning
confidence: 99%